Knowledge, attitude and practices towards pharmacovigilance among health care professionals in a teaching and general hospital of South India - Ghazala, Zainab; Kalshetty, Prakash; Vardhamane, Shrenik (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Pharmacovigilance is the science and activities relating to detection, monitoring, assessment, understanding and prevention of adverse effects or any other drug related problem from any pharmaceutical products. The core purpose of pharmacovigilance is to enhance patient care and generate the evidence based information on safety of medicines. The objective of present study was to evaluate the knowledge, attitude and practices of the healthcare professionals about pharmacovigilance and to assess the reasons for underreporting of ADRs. Methods: A cross-sectional study was conducted by administering KAP questionnaire to the healthcare professionals. There were 22 multiple choice questions. Ten related to knowledge, 5 related to attitude, and 6 related to practice. One question was asked to determine the reasons for underreporting of ADRs. The performance in each category was graded as good, average and poor if the number of participants giving correct/positive responses were >70%, 50-69%, <50% respectively. Question no 22 was assessed independently to find out reasons for underreporting of ADRs. Data was compiled and analyzed by descriptive statistics, Chi-square and ANOVA test. Results: The response rate in this study was 62.5%. The study included professors (11%), associate professors (6%), assistant professors (20%), postgraduates (26%) and interns (37%). That there was statistically very highly significant difference of mean score of knowledge, attitude and practice among health care professionals (P<0.001). The performance score with respect to attitude of health care professionals towards pharmacovigilance was good as compared to knowledge which was average followed by practice which showed poor performance (72.5% >51.6% >36.8%) (p <0.001). Conclusions: Awareness campaigns, CMEs, workshops on pharmacovigilance should be conducted regularly such that good knowledge about pharmacovigilance can be imparted which can be moulded into good practice.